آلية تنظيم العلاقة بين المهندس المعماري والمهندس المدني - مصلح سلمان محمد; فاضل مخيبر اشواق (Journal of Engineering and Sustainable Development, 2010)
The complication of design operation becomes rising by increasing of limits and effects in the different building systems (architecture, structure, services.. etc), that correlate with sociality, behaviorism and cultural developments which affected by technological developments architecture and structure (and what correlate with the design decision decision members). Therefore, all of the reveal an importance of arrangement mechanisum of relationship between architect and structural engineer and importance effects in design operation and architectural product, in order to enabling these members to treat all problems and obstacles with completeness and success. So the research problem reveald by the depth view absence of arrangement mechanisum importance (especially in the practiced level in the design operation) as a nature of the interdependence relationship among the design operation members and that appears the gap between those members through the place and time, which requires revealing the large role of arrangement mechanisum of relationship between architectural and structural engineer. So that, the research aims to high light the importance of role this mechanisum in that relationship in many levels of connections in order to get the best design functional criterion and then achieve the design creation, and the search reper the big importance of cultural level and the method of architect and structural engineering and the role of colleges in basic studies and high studies to explain the relationship among the members of design job.